Забезпечення та захист конституційної законності Конституційним Судом України - Шевчук, Ірина Миколаївна; Shevchuk, I. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті досліджено діяльність Конституційного Суду України як органу конституційного контролю щодо забезпечення та захисту конституційної законності, піддано аналізу теоретичні та практичні питання вдоско- налення його правового статусу. Визначено, що Конституційний Суд України є важливим інститутом забезпе- чення й захисту конституційної законності через здійснення конституційного контролю та інтерпретаційної діяльності. The article deals with the activity of the Constitutional Court of Ukraine as the body of constitutional control over ensuring and protection of constitutional legality. It has been defined that the Constitutional Court of Ukraine is an important institution of ensuring and protection of constitutional legality through the implementation of constitutional control and interpretative activities. It has been found out that constitutional control is to ensure supremacy and direct effect of the Constitution of Ukraine throughout the state, prevents unconstitutional acts and provides constitutional legality. Interpretative activity of the Constitutional Court of Ukraine, which helps to ensure strict compliance and effective application of legal norms, and improves legal fundamentals for the functioning of public authorities, which aims at supporting their actions within constitutional law is important to ensure constitutional legality. It is noted that the effectiveness of the constitutional legality the Constitutional Court of Ukraine provides is negatively affected by the absence of a clear mechanism for implementation of its decisions.
Ensuring and Protection of Constitutional Legality by the Constitutional Court of Ukraine.
Keywords: законність; конституційна законність; Конституція України; legality; constitutional legality; the Constitution of Ukraine